2019
DOI: 10.7494/csci.2019.20.4.3163
|View full text |Cite
|
Sign up to set email alerts
|

Current research opportunities of image processing and computer vision

Abstract: Image processing and computer vision is an important and essential area in today’s scenario. Several problems can be solved through computer vision techniques. There are a large number of challenges and opportunities which require skills in the field of computer vision to address them. Computer vision applications cover each band of the electromagnetic spectrum and there are numerous applications in every band. This article is targeted to the research students, scholars and researchers who are interested to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…After the diagnosis of the first Covid case in 2019, several Deep Learning and Machine Learning based approaches like ChexNet [26], ChestNet [31], have been proposed to detect Covid-19. Image segmentation [9,22] can also be used for identifying the location and severity of the Covid. Most of the AI-based approaches used for the Covid detection use the pre-trained model because the publicly available dataset for the research number is small in size.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…After the diagnosis of the first Covid case in 2019, several Deep Learning and Machine Learning based approaches like ChexNet [26], ChestNet [31], have been proposed to detect Covid-19. Image segmentation [9,22] can also be used for identifying the location and severity of the Covid. Most of the AI-based approaches used for the Covid detection use the pre-trained model because the publicly available dataset for the research number is small in size.…”
Section: Related Workmentioning
confidence: 99%
“…This paper shown the comparative analysis of four different pre-trained model for Covid detection. Based on the result shown in Tables 8,9,10,1,12,13,14,15,16,17,18,and 19 and Figs. 10,11,12,13,14,15 and 16, it can be concluded that the InceptionResnetV2 model performs well as compare to the other pre-trained model.…”
Section: Performance Evaluation Of Mobilenetv2mentioning
confidence: 99%
“…It is used for semantic segmentation followed by instance segmentation. Later various extensions in the UNET model have been used to enhance its ability and solve several challenges in medical image segmentation 16,17 . In 2019, SegTHOR international competition was held on the topic “Automatic Segmentation of Organs at risk in Thoracic CT images.” Trullo et al, 18 the competition organizer, proposed a deep learning‐based technique for thoracic OAR segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of deep learning, more and more researchers pay attention to this hot field [20]. Facial expression recognition integrates many technologies such as machine learning, pattern recognition, and computer vision.…”
Section: Introductionmentioning
confidence: 99%